1997
DOI: 10.1086/514103
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Recurrent Genital Herpes with Recombinant Herpes Simplex Virus Type 2 Glycoproteins D and B: Results of a Placebo‐Controlled Vaccine Trial

Abstract: To determine the safety, immunogenicity, and efficacy of a recombinant herpes simplex virus type 2 glycoprotein D and B vaccine in the treatment of recurrent genital herpes, a randomized, placebo-controlled trial was held at two referral centers. Healthy patients with 4-14 recurrences per year received injections of both glycoproteins in MF59 adjuvant or of MF59 alone at 0, 2, 12, and 14 months. For 18 study months, the rate and number of recurrences, the duration and severity of the first confirmed recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
97
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(101 citation statements)
references
References 14 publications
0
97
0
4
Order By: Relevance
“…Rigorous clinical trials with only a few of these candidate vaccines have been performed. The largest such studies showed that recombinant HSV-2 glycoproteins B and D (gB2 and gD2, respectively) in a lipid emulsion adjuvant failed to protect against HSV-2 infection or disease (8,35), while more recent studies found gD2 in alum-monophosphoryl lipid A adjuvant to protect only women who had never been infected with either HSV serotype (31).…”
mentioning
confidence: 99%
“…Rigorous clinical trials with only a few of these candidate vaccines have been performed. The largest such studies showed that recombinant HSV-2 glycoproteins B and D (gB2 and gD2, respectively) in a lipid emulsion adjuvant failed to protect against HSV-2 infection or disease (8,35), while more recent studies found gD2 in alum-monophosphoryl lipid A adjuvant to protect only women who had never been infected with either HSV serotype (31).…”
mentioning
confidence: 99%
“…Most have been safe and have induced a measurable immune response. Although the first study of a recombinant gD2 vaccine adjuvanted with alum reduced the rate of virologically confirmed recurrences (106), later studies of glycoprotein vaccines failed to replicate that effect (107). Unlike the prophylactic vaccine studies, shedding data from our group indicate that the pivotal therapeutic vaccine studies can be performed efficiently with fewer than 100 individuals if viral shedding is used as an endpoint (33), whereas prophylactic vaccination studies require a much larger sample size.…”
Section: Human Clinical Trials Prophylactic Vaccines Testing Prophylmentioning
confidence: 91%
“…The most population-prevalent CD8 antigen was encoded by UL39. This 1,137-amino-acid-long polypeptide is the large subunit of ribonucleotide reductase, is not detected in virions, and is a virulence CD8 responses to HSV-1 proteins gD1 and gB1 were of special interest because they share high sequence homology with HSV-2 proteins that have been used as vaccine candidates (2,(43)(44)(45). HLA-A*0201-restricted CD8 epitopes have been previously reported in both HSV-1 and HSV-2 (16,17).…”
Section: Hsv-1-specific Cd8 + T Cells Can Be Detected and Enriched Bymentioning
confidence: 99%